منهج القرآن الكريم في التعامل مع الأزمات: دراسة موضوعية - محمد، هناء أحمد محمود (مجلة الدراية: مجلة علمية محكمة نصف سنوية., 2023)
This research deals with a set of Quranic rules related to confronting crises, and how to deal with them. one of its most important goals is to clarify the concept of crises and clarify that they are a feature of life, to show the wisdom of their existence, to know the most important measures that prevent them and prevent their occurrence, and to stand on the approach of the Holy Quran in treating them, and how to deal with it. this research relied on the analytical descriptive approach, as it followed the Quranic verses that dealt with this subject with study and analysis to reach the most important results and objectives. the study resulted in several results, the most important of which are: the intensity of the need in this era for the gifts of the holy Qur’an in crises, and its disclosure, as it showed that the Holy Qur’an provided effective treatment for crises through a unique approach, and legislation based on justice, equality, and Islamic brotherhood, in which it excels over laws situation, and recent studies that failed to do so. the study also showed that adhering to Islamic values and morals is one of the most important reasons that reduce crises and lead to mitigating their effects, which makes returning to the origins and principles of Islam an essential requirement. يتناول هذا البحث مجموعة من القواعد القرآنية المتعلقة بمواجهة الأزمات، وكيفية التعامل معها، ويهدف إلي بيان مفهوم الأزمات التي أصبحت سمة من سمات الحياة، والحكمة من وجودها، ومعرفة أهم الإجراءات التي تمنع حدوثها، والوقوف على منهج القرآن الكريم في علاجها، وكيفية التعامل معها. معتمدة في ذلك على المنهج الوصفي التحليلي والمنهج الاستقرائي حيث قمت بتتبع الآيات القرآنية التي تناولت هذا الموضوع بالدراسة والتحليل للوصول إلى أهم النتائج والأهداف. وقد أسفرت الدراسة عن عدة نتائج من أهمها: شدة الحاجة في هذا العصر إلى هدايات القرآن الكريم في الأزمات، والكشف عنها، وأن القرآن الكريم قدم علاجا فعالا للأزمات من خلال منهج متفرد، وتشريعات قائمة على العدل والمساواة والأخوة الإسلامية، تفوق القوانين الوضعية، والدراسات الحديثة التي عجزت عن ذلك. كما أظهرت الدراسة أن التمسك بالقيم الإسلام وآدابه من أهم الأسباب التي تقلل الأزمات، وتؤدي إلى التخفيف من آثارها، مما يجعل العودة إلى أصول الإسلام ومبادئه مطلبا أساسيا.